2014
DOI: 10.1590/s0100-736x2014000600005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the 2,4-D herbicide on gills epithelia and liver of the fish Poecilia vivipara

Abstract: Pesq. Vet. Bras. 34(6):523-528, junho 2014 523 RESUMO.-[Efeitos do herbicida 2,4-D no epitélio das brânquias e no fígado do peixe Poecilia vivípara.] A toxicidade aguda do herbicida 2,4-D foi investigada através dos efeitos no peixe Poecilia vivípara (Bloch et Schneider, 1801). Grupos de peixes foram expostos ao herbicida nas concentrações de 10, 20 e 40ml por litro de água, durante 24 horas. As brânquias e o fígado foram estudados. A concentração letal média (CL50) do herbicida para a espécie em questão… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Changes in the circulatory system such as vasodilation and aneurysms indicate increased blood vessels pressure. Such histological alterations in fish gills have also been reported in other studies such as Campagna et al (2007); Peebua et al (2008); Ramírez-Duarte et al (2008); Vigário and Sabóia-Morais (2014) under the influence of different pesticides. The present study found aneurysms, which actually were not observed in the common carp gills when it was exposed to thiamethoxam.…”
Section: Resultssupporting
confidence: 83%
“…Changes in the circulatory system such as vasodilation and aneurysms indicate increased blood vessels pressure. Such histological alterations in fish gills have also been reported in other studies such as Campagna et al (2007); Peebua et al (2008); Ramírez-Duarte et al (2008); Vigário and Sabóia-Morais (2014) under the influence of different pesticides. The present study found aneurysms, which actually were not observed in the common carp gills when it was exposed to thiamethoxam.…”
Section: Resultssupporting
confidence: 83%
“…The results suggest that exposure to the active ingredient in these formulations, 2,4‐D, is responsible for the negative survival impacts. In contrast, the literature has shown that pure 2,4‐D compounds had no effect on survival at low, ecologically relevant concentrations on older juvenile and adult fathead minnows (US Environmental Protection Agency ; Coady et al ; Vigário and Sabóia ). To our knowledge, no published studies have tested the impacts of environmentally relevant doses (0.00–2.00 ppm) of pure 2,4‐D exposure on survival from fertilization to 14 dph in any fish species.…”
Section: Discussionmentioning
confidence: 95%
“…There is a lack of information about the occurrence of 2,4‐D in aquatic ecosystems, but the present study indicates that 2,4‐D is a frequent pollutant in surface water of agricultural areas, and it should be included in monitoring programs. Also, it is relevant to study the presence of 2,4‐D in surface water because it can induce adverse effects on aquatic biota, as reported by Vigário and Sabóia‐Morais in the South American fish Poecilia vivipara .…”
Section: Discussionmentioning
confidence: 99%